Effectiveness of Vitamin D Therapy on the Lipid Profile of Patients with Polycystic Ovary Syndrome - Usman, Fatimah; Abadi, Adnan; Effendi, Kms. Yusuf; Manan, Heriyadi; Andrina, Hana (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2024)
Polycystic ovary syndrome (PCOS) is characterized by chronic hyperandrogenism and anovulation that is also associated with various clinical and biochemical features. Vitamin D deficiency is a common problem that affects up to half of the adult population worldwide, including patients with PCOS. Based on these considerations, we are interested in further exploring the effectiveness of vitamin D in improving lipid profiles in PCOS.Efektivitas Terapi Vitamin D pada Profil Lipid Penderita Sindrom Ovarium PolikistikAbstrakSindrom Ovarium Polikistik (PCOS) ditandai dengan hiperandrogenisme kronis dan anovulasi yang juga berhubungan dengan berbagai gambaran klinis dan biokimia. Kekurangan vitamin D adalah masalah umum yang mempengaruhi setengah populasi orang dewasa di seluruh dunia, termasuk pasien PCOS. Tinjauan literatur ini dilakukan untuk mencari artikel asli dan review mengenai pertanyaan spesifik mengenai efektivitas terapi vitamin D terhadap profil lipid pasien PCOS.Kata kunci: PCOS, Lipid, Vitamin D